2008
DOI: 10.2174/156720208785425675
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin Polymorphism and Lacunar Stroke

Abstract: Haptoglobin (Hp) 2-2 phenotype has been associated with peripheral and coronary artery disease and risk of vascular complications in diabetic patients, but any association of Hp polymorphism with cerebrovascular disease has not been explored so far. We aimed to study Hp polymorphism in a sample of 124 patients with a rather homogeneous type of cerebrovascular disease, namely first symptomatic lacunar stroke due to small vessel disease, in comparison with a large (n=918) control group. Hp phenotypes were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 0 publications
3
37
2
Order By: Relevance
“…Taken together, these findings suggest an adverse effect of vitamin E therapy in carriers of the Hp 1 allele, which could be due to exacerbation of a potential stroke susceptibility in the Hp 1-1 group, should findings in the general population (5-7) hold true also in diabetes. To our knowledge, however, such assessments in diabetes have yet to be conducted.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Taken together, these findings suggest an adverse effect of vitamin E therapy in carriers of the Hp 1 allele, which could be due to exacerbation of a potential stroke susceptibility in the Hp 1-1 group, should findings in the general population (5-7) hold true also in diabetes. To our knowledge, however, such assessments in diabetes have yet to be conducted.…”
Section: Introductionmentioning
confidence: 72%
“…Specifically, compared to healthy volunteers, a greater frequency of the Hp 1 allele was found among patients with a first symptomatic small vessel lacunar stroke and Hp 1 was also related to white matter lesions (5). Similarly to our findings, the direct effect of the Hp 1 allele appeared more pronounced among those with hypertension, while an association was absent in normotensive individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic ischemia in frontal white matter could interrupt frontal-cerebellar circuits, induce hypometabolism in cerebellar regions, and decrease perfusion and apparent diffusion coefficient (ADC) [43] . for MTHFR C677T, ApoE/epsilon4 or PAI-A 4G/5G polymorphism [44] . Analysis of haptoglobin (Hp) 2-2 phenotype in a group of patients with first symptomatic lacunar stroke has revealed that Hp1 allele frequency is significantly higher than that in control group, mainly due to a lower Hp2-2 phenotype frequency.…”
Section: Hypoperfusion/ischemic Injury Previous Reportsmentioning
confidence: 95%
“…Hp Gene P00737 Hp1-1 phenotype has been associated with SVD stroke patients in the chronic stage (124 patients included in the study) [75] Hcy Amino acid Involved in vascular damage. High levels of Hcy associated with SVD stroke in different population studies including all etiologies.…”
Section: Biomarkers That Have Been Assayed In Stroke Patientsmentioning
confidence: 99%